EFEKTIVITAS PEMASARAN DIGITAL PADA BANK SYARIAH DI INDONESIA - Gita Putri Oktaviani; Muhammad Iqbal Fasa (Cipta Kind Publisher, 2024)
This study investigates the effectiveness of digital marketing strategies employed by Islamic banks in Indonesia. With the increasing use of the internet and social media, Islamic banks have adopted digital marketing to reach broader audiences efficiently. Digital marketing enables banks to not only reduce costs but also track campaign effectiveness in real-time, allowing for swift adjustments. The study highlights that creative content, particularly on platforms like Instagram, successfully attracts younger generations, a crucial demographic for Islamic banks. Moreover, partnerships with fintech companies offer opportunities to further expand market reach. Despite these successes, challenges persist, such as ensuring a secure and user-friendly digital experience to maintain customer trust and satisfaction. Findings suggest that digital marketing strategies have positively influenced market penetration and service quality for Islamic banks. Continued innovation in content and strategy refinement is essential for long-term growth in the Islamic banking sector. Further research is recommended to assess the long-term impact of these strategies on the sector’s development.